1998
DOI: 10.1002/(sici)1099-1298(199801/02)8:1<1::aid-casp435>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Police interviewing and psychological vulnerabilities: predicting the likelihood of a confession

Abstract: This paper is concerned with examining the differences between people who confess and those who deny offences during a police interview. The main hypothesis under investigation is that psychologically vulnerable suspects are particularly likely to confess. This paper is also concerned with identifying variables that might be related to the confession process. One hundred and sixty suspects detained at two London police stations were assessed psychologically prior to being interviewed by the police. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 25 publications
3
72
1
Order By: Relevance
“…In the United States, however, interrogation can proceed only if police inform suspects of their Miranda rights to remain silent and to consult an attorney (based on the Supreme Court's Miranda v. Arizona case of 1966), and suspects then waive these rights. The act of suspects' invoking their Miranda rights forestalls interrogation, and research shows that consulting an attorney dramatically decreases the likelihood of a confession (Pearse, Gudjonsson, Clare, & Rutter, 1998;Moston, Stephenson, & Williamson, 1992). However, research suggests that investigators are skilled at influencing suspects to waive their Miranda rights, and the majority do (Leo, 1996;Leo & White, 1999).…”
Section: Relevant Criminological and Psychological Research On Confesmentioning
confidence: 99%
“…In the United States, however, interrogation can proceed only if police inform suspects of their Miranda rights to remain silent and to consult an attorney (based on the Supreme Court's Miranda v. Arizona case of 1966), and suspects then waive these rights. The act of suspects' invoking their Miranda rights forestalls interrogation, and research shows that consulting an attorney dramatically decreases the likelihood of a confession (Pearse, Gudjonsson, Clare, & Rutter, 1998;Moston, Stephenson, & Williamson, 1992). However, research suggests that investigators are skilled at influencing suspects to waive their Miranda rights, and the majority do (Leo, 1996;Leo & White, 1999).…”
Section: Relevant Criminological and Psychological Research On Confesmentioning
confidence: 99%
“…In a follow-up study to that carried out by Gudjonson, Clare, Rutter, and Pearse (1993) for the Royal Commission on Criminal Justice, Pearse, Gudjonsson, Clare, and Rutter (1998), found that of a number of psychological and context variables analysed, one predicted a confession and two predicted a denial. The factor that predicted a confession was if the suspect reported having taken illicit drugs within 24 hours of the interrogation.…”
mentioning
confidence: 91%
“…Comparing these rates is difficult because several legal, judicial, and methodological factors can influence these confession rates (Gudjonsson, 2003;Kassin & Gudjonsson, 2004;St-Yves, 2004). Whereas some of the US studies have revealed confession rates varying 42-47% (Cassell & Hayman, 1998;Leo, 1996), studies conducted in the UK revealed confession rates varying 55-59% (Moston & Stephenson, 1994;Pearse et al, 1998;Phillips & Brown, 1998; see, however, Moston, Stephenson, & Williamson, 1992 Gudjonsson, 2003;St-Yves & Landry, 2004;Williamson, 1992).1 Sampling criteria and the types of cases studied can also influence the confession rate.2 Gudjonsson (2003) raised the possibility that the method selected to collect information about confessions (e.g., observation, police records, survey) might influence the confession rate. To our knowledge, no study has shown that one method is superior 1 In the UK, the law permits no ruses or persuasive techniques to be used during the interrogation.…”
mentioning
confidence: 99%
“…Previous studies revealed mixed results as to the role of age on the offender's decision to confess, with several studies reporting a negative relationship between the suspect's age and the likelihood of a confession (Baldwin & McConville, 1980; Beauregard, Deslauriers-Varin, & St-Yves, under review;Pearse et al, 1998;Phillips & Brown, 1998;Softley, 1980), whereas other studies revealed no relationship (Leo, 1996;Mitchell, 1983;Moston et al, 1992;Neubauer, 1974;St-Yves, 2002). Mixed results have also been reported for the role of ethnicity, as some researchers reported evidence that Caucasians were more likely to confess compared to non-Caucasians (Leo, 1996;Phillips & Brown, 1998;St-Yves, 2002).However, two studies failed to replicate this finding (Pearse et al, 1998;Wald, Ayres, Hess, Schantz, & Whitebread, 1967). Only one study looked at the impact of the offender's civil status CONFESSING THEIR CRIME 6 on the confession rate (St-Yves, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation